Genetic and cellular characterization of MscS-like putative channels in the filamentous fungus Aspergillus nidulans - Mariangela Dionysopoulou; Nana Yan; Bolin Wang; Christos Pliotas; George Diallinas (Channels, 2022)
Mechanosensitive ion channels are integral membrane proteins ubiquitously present in bacteria, archaea, and eukarya. They act as molecular sensors of mechanical stress to serve vital functions such as touch, hearing, osmotic pressure, proprioception and balance, while their malfunction is often associated with pathologies. Amongst them, the structurally distinct MscL and MscS channels from bacteria are the most extensively studied. MscS-like channels have been found in plants and Schizosaccharomyces pombe, where they regulate intracellular Ca2+ and cell volume under hypo-osmotic conditions. Here we characterize two MscS-like putative channels, named MscA and MscB, from the model filamentous fungus Aspergillus nidulans. Orthologues of MscA and MscB are present in most fungi, including relative plant and animal pathogens. MscA/MscB and other fungal MscS-like proteins share the three transmembrane helices and the extended C-terminal cytosolic domain that form the structural fingerprint of MscS-like channels with at least three additional transmembrane segments than Escherichia coli MscS. We show that MscA and MscB localize in Endoplasmic Reticulum and the Plasma Membrane, respectively, whereas their overexpression leads to increased CaCl2 toxicity or/and reduction of asexual spore formation. Our findings contribute to understanding the role of MscS-like channels in filamentous fungi and relative pathogens.